Health system barriers and predictors of prenatal care utilization at a large academic medical center - Molly Klare; Amanda Miyuki Dougherty; Melody Chang; Amberly Mendes; Scott Graziano (Springer, 2024)
Abstract Introduction This retrospective cohort study recognizes a profound need to address rising rates of maternal morbidity and mortality, especially its disproportionate impact on ethnic and racial minorities. Timely access to high-quality prenatal care is essential, the absence of which is associated with increased risk of adverse maternal and fetal outcomes. The persistence of racial and ethnic disparities in pregnancy outcomes, despite accounting for income and education level, suggests that barriers to care are also significantly limited by psychosocial and health system barriers. Methods This retrospective cohort study analyzed several potential barriers to prenatal care among postpartum patients who delivered at Loyola University Medical Center in Maywood, Illinois, such as transportation, parking, childcare, clinic wait times, scheduling difficulties, and knowledge about the impact of COVID-19 on pregnancy. Participants were screened daily for eligibility and consented to participate from February to May 2022, a total of three months. Eligible patients were given a 10-question paper survey that also assessed out-of-pocket costs and suggestions to improve prenatal care attendance and satisfaction. During the study period, there were 251 eligible deliveries. 197 patients (77.3%) were consented and participated in the survey. 194 (98.4%) were eligible for post-chart review; 21 patients (10.6%) declined to participate, 33 patients (16.8%) did not complete the survey, and 3 surveys (1.5%) were lost. Retrospective chart reviews were conducted for PNC utilization, pregnancy comorbidities and outcomes, and demographic information. Data underwent Fischer analyses, chi-squared analyses, and ANOVAs. Institutional Review Board-approved, participants consented for research and quality improvement, including medical record data use. Results Among 194 patients, average reported barriers to PNC were 2.14, with "difficulty scheduling appointments" (39.6%) and "couldn't leave work or school" (30.2%) most common. Despite most patients reporting a similar number of barriers, timing disparities based race and ethnicity, education, and income were observed. Hispanic patients initiated PNC later than non-Hispanic White patients (13w6d vs. 10w5d; p = 0.009). Twelfth-grade education or less initiated PNC bachelor's degree holders (16w vs. 11w; p < 0.001). Patients who made < 45 k annually initiated later than > 140 k (13w3d vs. 9w1d; p = 0.02). Patients who reported "long wait times" initiated prenatal care an average of 2w2d later than patients not facing this barrier, at 14w1d vs. 12w0d, respectively (p = 0.01). Conclusions Lower socioeconomic status and ethnic minority patients exhibit delayed PNC start that are linked to adverse outcomes. Noteworthy discrepancies within the surveyed cohorts, despite comparable reported barriers, hint at the existence of supplementary, interconnected obstacles specific to these patients. Future efforts should tackle common issues specific to various sociodemographic groups to address disparities in pregnancy outcomes.